2014
DOI: 10.1002/jbm.b.33169
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance evaluation of a positive reference material for hemolysis testing

Abstract: This study deals with the development and performance evaluation of a positive reference material for hemolysis testing, which is used for evaluating the biological safety of medical devices. Genapol X-080, a nonionic detergent, was selected as a candidate hemolytic substance in a survey of 23 chemical compounds; it showed significant hemolytic activity against rabbit defibrinated blood at concentrations more than 20 µg/mL. A polyvinyl chloride (PVC) sheet spiked with 0.6% (w/w) of the compound exhibited weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Previously, we found that Y‐2 and Y‐4 sheets elicit weak or strong hemolysis, respectively, in direct contact and/or extract‐based assays . There is a clear relationship between the degree of hemolytic activity and elution volume for Genapol X‐080 .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Previously, we found that Y‐2 and Y‐4 sheets elicit weak or strong hemolysis, respectively, in direct contact and/or extract‐based assays . There is a clear relationship between the degree of hemolytic activity and elution volume for Genapol X‐080 .…”
Section: Discussionmentioning
confidence: 86%
“…Previously, we found that Y-2 and Y-4 sheets elicit weak or strong hemolysis, respectively, in direct contact and/or extract-based assays. 7 There is a clear relationship between the degree of hemolytic activity and elution volume for Genapol X-080. 7 Using the direct contact method, the amount of Genapol X-080 eluted from Y-2 and Y-4 sheets into blood samples increases over time, reaching 25.6 or 1154 lg/mL after incubation at 378C for 4 h, corresponding to approximately the CMC, and substantially higher than the CMC, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations